Clinical Significance of Epidurography Contrast Patterns after Adhesiolysis during Lumbar Percutaneous Epidural Neuroplasty - Park, Sang-Hyuk (Pain Res Manag, 2018)
BACKGROUND: The correlation between epidurography contrast patterns and the clinical outcomes of percutaneous epidural neuroplasty (PEN) remains unclear. OBJECTIVE: To analyze the correlation between postadhesiolysis epidurography contrast patterns and the clinical outcomes of patients who undergo lumbar PEN. DESIGN: This study is a retrospective analysis of 78 consecutive patients who underwent lumbar PEN between April 2012 and March 2013. SETTING: The analysis was done in the university hospital center. METHOD: The clinical outcomes of all patients were assessed before and 1, 3, 6, and 12 months after undergoing lumbar PEN. Specifically, the intensity of back and leg pain, quality of life, and procedural outcomes were evaluated using a visual analog scale (VAS), the Oswestry Disability Index (ODI), and the 12-Item Short-Form Health Survey (SF-12). RESULTS: The VAS scores for back and leg pain, ODI score, and SF-12 score exhibited a significant improvement during the follow-up period (P < 0.01 versus preprocedural scores). At most follow-up time points, patients exhibiting extraforaminal contrast distribution (n=22) on postadhesiolysis epidurograms exhibited a similar improvement in VAS scores and a significantly better improvement in ODI and SF-12 scores compared with patients exhibiting intracanal contrast distribution (n=56). CONCLUSION: Extraforaminal contrast distribution during lumbar PEN may be associated with better functional outcomes.